2010
DOI: 10.1590/s0104-11692010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for breast neoplasm in the city of Maringá, Paraná state, Brazil

Abstract: The aim of this study was to identify the prevalence of the risk factors for breast cancer among women between 40 and 69 years old in the city of Maringá, Paraná State, Brazil.An analytical, exploratory and cross-sectional study was carried out through a population research at homes in Maringá. The sample was composed of 439 women between 40 and 69 years old. The data were collected by home interviews, stored using the Statistical Package for the Social Sciences (SPSS) software and presented in tables as absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 11 publications
7
15
2
5
Order By: Relevance
“…For instance, Paiva et al (29), in a case-control study observed a family history of breast cancer in 12.5% of the patients with breast cancer and in 13.1% of the controls. Matos et al (30) also showed the prevalence of the disease in 2.3% mother, 3.9% sister and 0.2% daughter affected by the disease.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, Paiva et al (29), in a case-control study observed a family history of breast cancer in 12.5% of the patients with breast cancer and in 13.1% of the controls. Matos et al (30) also showed the prevalence of the disease in 2.3% mother, 3.9% sister and 0.2% daughter affected by the disease.…”
Section: Discussionmentioning
confidence: 92%
“…This interpretation was supported by the fact that Latin American authors of 25 studies on the risk of BC mainly cited international literature published in English. There were only two exceptions of studies whose authors cited mainly previous publications of their own country written in Spanish and Portuguese 22,23 . In contrast, 16 studies on the knowledge and awareness about BC cited mainly previous publications of their own country written in Spanish or Portuguese (p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, three authors identified increased educational level as risk factor (Chart 2) 34,36,40 . Decreased educational level may explain increased risk of non-participation on screening programs and BSE in three out of four studies (Chart 2) 22,29,50 . This argument cannot explain the results of Inamuru et al, who compared in a case-control study several reproductive risk factors among women from rural regions and urbanized centres of Mid-western Brazil (Chart 2) 37 : Additionally, the authors of this study also identified lower income and decreased educational level as risk factors for women living in rural areas (Chart 2) 37 .…”
Section: Education and Income Were Context-dependent Risk Factors Of mentioning
confidence: 98%
See 2 more Smart Citations